Tata kelola administrasi pada laporan pertanggung jawaban Dana Desa di Desa Sendangan Kec.Tompaso, Kabupaten Minahasa - Laurents, Anthonius; POSUMAH, JOHNNY; TULUSAN, FEMMY (Sam Ratulangi University, 2019)
This study aims to describe how the implementation of administrative governance in reporting village funds. This study uses descriptive qualitative methods, and data collection techniques used are observation, interview and documentation. The number of informants in this study were seven people. In this study using the theory of good governance principles. The results of this study indicate that in administrative governance of village fund reporting in rural areas, not all village administrations can be applied in accordance with applicable regulations that refer to PERMENDAGRI No. 47 of 2016. The lack of tools needed to manage village administration, and the lack of capacity and responsibility of the village government in carrying out its duties, and the implementation of work duties that are not in accordance with the basic tasks and functions of village officials, are obstacles to achieving good and appropriate administrative governance in the village fund accountability report. .Keywords: Governance, Village Administration, Responsibility Report, Village Fund